Constants in the historical process of the Congregation of Saint Dorothea... Current work, lines that do not break! - Irmã Maria Lúcia Ferreira Soares (Escola Superior de Educação de Paula Frassinetti, 2016)
Article about the origin, history and current relevance of youth education in the Congregation of Saint Dorothea.